Mutational consequences of dNTP pool imbalances in E. coli - Schaaper, Roel M. (2012)
The accuracy of DNA synthesis depends on the accuracy of the polymerase as well as the quality and concentration(s) of the available 5′-deoxynucleoside-triphosphate DNA precursors (dNTPs). The relationships between dNTPs and error rates have been studied in vitro, but only limited insights exist into these correlations during in vivo replication. We have investigated this issue in the bacterium E. coli by analyzing the mutational properties of dcd and ndk strains. These strains, defective in dCTP deaminase and nucleoside diphosphate kinase, respectively, are characterized by both disturbances of dNTP pools and a mutator phenotype. ndk strains have been studied before, but were included in this study, as controversies exist regarding the source of its mutator phenotype. We show that dcd strains suffer from increased intracellular levels of dCTP (four-fold) and reduced levels of dGTP (two-fold), while displaying, as measured using a set of lacZ reversion markers in a mismatch-repair defective (mutL) background, a strong mutator effect for G·C→T·A and A·T→T·A transversions (27- and 42-fold enhancement, respectively). In contrast, ndk strains possess a lowered dATP level (four-fold) and modestly enhanced dCTP level (2-fold), while its mutator effect is specific for just the A·T→T·A transversions. The two strains also display differential mutability for rifampicin-resistant mutants. Overall, our analysis reveals for both strains a satisfactory correlation between dNTP pool alterations and the replication error rates, and also suggests that a minimal explanation for the ndk mutator does not require assumptions beyond the predicted effect of the dNTP pools.